Three Tier Test Diagnostik untuk Mengidentifikasi Kategori Miskonsepsi Siswa pada Materi Statistika - Fajri, Chusshila; Yanti, Aning Wida; Suparto; Supranoto (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to identify misconceptions among 10th grade students at MAN 1 Lamongan regarding statistics, particularly the concept of data centralization. The study uses a qualitative descriptive method with a sample of 30 students selected through random sampling. The instrument is a three-tier diagnostic test consisting of five items. The test not only assesses correct or incorrect answers but also evaluates students' reasoning and level of confidence. Misconception indicators were analyzed based on a combination of answers at three levels, resulting in the following categories: understanding the concept, misconception, guessing, lucky guess, and lack of knowledge. The level of misconception was then classified into low (0%-30%), medium (31%-60%), and high (61%-100%). The results of the study show that students' misconceptions are in the moderate category, namely 58%, particularly in the concept of calculating data values based on average values. This is influenced by a lack of understanding of the meaning of the concept of average and the minimal variation in contextual questions given by teachers. The three-tier test instrument has been proven to be able to identify specific categories of misconceptions, so that it can be used as a reference for teachers in designing more appropriate learning strategies that are oriented towards conceptual understanding.